Synesthesia: a colorful word with a touching sound? - Mylopoulos, Myrto I.; Ro, Tony (Frontiers in Psychology, 2013)
Synesthesia is a fairly common condition in which individuals experience atypical responses (such as color experiences) in association with certain types of stimuli (such as non-colored letters). Although synesthesia has been described for centuries, only very recently has there been an explosive growth of systematic scientific examinations of this condition. In this article, we review and critically evaluate current methods for both assessing synesthesia and examining its psychological basis, including the "test-retest" procedure, online battery assessments, and behavioral experiments. We highlight the limitations of these methods for understanding the nature of this complex condition and propose potential solutions to address some of these limitations. We also provide a set of characteristics that aid in distinguishing synesthesia from other closely related psychological phenomena.